2012
DOI: 10.1042/cbi20110088
|View full text |Cite
|
Sign up to set email alerts
|

Resistance against tumour necrosis factor α apoptosis by the cellular prion protein is cell‐specific for oral, colon and kidney cancer cell lines

Abstract: Since the discovery of PrPC (cellular prion protein), most studies have focused on its role in neurodegenerative diseases, whereas its function outside the nervous system remains obscure. We investigated the ability of PrPC in resisting TNFα (tumour necrosis factor α) apoptosis in three PrPC-transiently transfected cancer cell lines, renal adenocarcinoma ACHN, oral squamous cell carcinoma HSC-2 and colon adenocarcinoma LS174T. PrPC-expressing ACHN and LS174T cells had higher viabilities compared with the mock-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…TNF-related apoptosis-inducing ligand (TRAIL), and antitumor drugs [7][8][9] and promoting tumorigenesis, proliferation, and G1/S cell cycle transition [10,11]. Similarly, our group also showed that PrP C confers resistance against apoptosis induced by tunicamycin (a N-linked glycosylation inhibitor), TNF-α, and H 2 O 2 oxidative stress in oral squamous cell carcinoma (HSC-2) and colon adenocarcinoma (LS 174T) cell lines [12,13].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…TNF-related apoptosis-inducing ligand (TRAIL), and antitumor drugs [7][8][9] and promoting tumorigenesis, proliferation, and G1/S cell cycle transition [10,11]. Similarly, our group also showed that PrP C confers resistance against apoptosis induced by tunicamycin (a N-linked glycosylation inhibitor), TNF-α, and H 2 O 2 oxidative stress in oral squamous cell carcinoma (HSC-2) and colon adenocarcinoma (LS 174T) cell lines [12,13].…”
Section: Introductionmentioning
confidence: 69%
“…Hence, the anti-Bax function might be attributed partly to the uncommon cytosolic form of PrP C , which has been shown to be protective against Bax-mediated cell death in human primary neurons and breast cancer MCF-7 cells [14]. However, the LS 174T cell line has null Bax expression [15], yet PrP C overexpression in this cell line was able to prevent against apoptosis by stimuli as mentioned earlier [12,13]. Hence, it is speculated that other pathways may be engaged by PrP C to exert its cytoprotection against apoptotic cell death, which exclude the participation of Bax.…”
Section: Introductionmentioning
confidence: 99%
“…Since other biologically interesting challenges appear to involve Prnp expression (e.g. ischemia, hypoxia and cancer; [62][67]) this mouse line could be a useful resource for researchers interested in studying the dynamics of Prnp activity in vivo . Moreover, induced pluripotent stem cells from these mice, and the ES cells used to generate them, may be useful for testing stem cell differentiation procedures and therapeutic transplantations for mouse models of many diseases, possibly being observed in living brains through cranial windows.…”
Section: Discussionmentioning
confidence: 99%
“…In the epithelial compartment, greater amounts of mRNA and proteins are found in the colon compared with the small intestine in mice 47 . PrP C is expressed in various amounts in different human colon adenocarcinoma cell lines such as Caco-2/TC7, 48 HT29, 46 LS174T, 49 SW480 and HCT116 (unpublished data). In Caco-2/TC7 enterocytes, PrP C is localized in lateral junction domains, in lipid rafts 48 , 50 .…”
Section: Prpc In Cell-cell Junctions and Barriersmentioning
confidence: 93%